Sex Differences in the Metabolome of Alzheimer's Disease Progression - González Zarzar, Tomás; Lee, Brian; Coughlin, Rory; Kim, Dokyoon; Shen, Li; Hall, Molly A. (Frontiers in Radiology, 2022)
Alzheimer's disease (AD) is the leading cause of dementia; however, men and women face differential AD prevalence, presentation, and progression risks. Characterizing metabolomic profiles during AD progression is fundamental to understand the metabolic disruptions and the biological pathways involved. However, outstanding questions remain of whether peripheral metabolic changes occur equally in men and women with AD. Here, we evaluated differential effects of metabolomic and brain volume associations between sexes. We used three cohorts from the Alzheimer's Disease Neuroimaging Initiative (ADNI), evaluated 1368 participants, two metabolomic platforms with 380 metabolites in total, and six brain segment volumes. Using dimension reduction techniques, we took advantage of the correlation structure of the brain volume phenotypes and the metabolite concentration values to reduce the number of tests while aggregating relevant biological structures. Using WGCNA, we aggregated modules of highly co-expressed metabolites. On the other hand, we used partial least squares regression-discriminant analysis (PLS-DA) to extract components of brain volumes that maximally co-vary with AD diagnosis as phenotypes. We tested for differences in effect sizes between sexes in the association between single metabolite and metabolite modules with the brain volume components. We found three metabolite modules and 76 single metabolites with significant differences between sexes. These results highlight a heightened lipid disruption in men, particularly associated with lower levels of alkyl-acyl phosphatidylcholines and higher levels of very-low density lipoproteins associated with AD development. On the other hand, we observed an impaired glucose metabolism in women, characterized by lower concentration levels of glucose and alanine. Explicitly identifying sex differences in metabolomics during AD progression can highlight particular metabolic disruptions in each sex. Our research study and strategy can lead to better-tailored studies and better-suited treatments that take sex differences into account.